Heterologous expression of the multi-functional cellulase gene (mfc) from the mollusc Ampullaria crossean, in Volvariella volvacea. Issue 4 (3rd July 2016) - Guo, Xin-Yue; Lin, Shu-Ling; Guo, Li-Qiong; Lin, Jun-Fang; Ye, Zhi-Wei
ABSTRACT: Volvariella volvacea, or straw mushroom, is a widely cultivated and important edible fungus. In this paper, we used straw mushroom as a host to express an exogenous mfc gene encoding a multi-functional cellulase (MFC) cloned from the mollusc Ampullaria crossean . The purpose was to increase expression of MFC in the new host, as well as to improve cellulose degradation and increase future yields of V. volvacea . MFC is an enzyme with exo- β -1, 4-glucanase, endo- β -1, 4-glucanase, and endo- β -xylanase activities. The A. crossean mfc gene was expressed in V. volvacea under the control of an endogenous promoter ( gpd -Vvs) using the expression vector pgVvs-mfc, constructed by ligating the gpd -Vvs promoter with the mfc gene. The expression plasmid, pgVvs-afp, containing an afp gene encoding an anti-freeze protein (AFP) cloned from spruce budworm as the selective marker gene, was co-transformed into protoplasts of V. volvacea along with the vector pgVvs-mfc using polyethylene glycol (PEG)-mediated transformation. Putative transformants of V. volvacea were obtained by exposing the mycelia to regeneration medium (200 g l − 1 potato extract, 20 g l − 1 dextrose, 20 g l − 1 agar, and 0.8 M D-mannitol) at 0°C. PCR and Southern blotting were used to identify positive transformants. The results indicated that the mfc gene had been integrated into the genome of V. volvacea . The total cellulose activity, based on filter paper degradation, and carboxymethyl cellulase and xylanase activities in the transformants were 3.92, 4.75, and 58.99 Units ml − 1, respectively. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis showed an approx. 46 kDa band, which was equivalent to the expected size of the MFC protein of A. crossean . Thus, the mfc gene appeared to have been expressed heterologously in V. volvacea .